Viability of Medium-Scale Vermicompost Plant: a Case Study in Kushtia, Bangladesh - Ibrahim, Abu Shahadat Md.; Mohammad, Ashif; Khalil, Md. Ibrahim; Shams, S. M Nasif (PT FORMOSA CENDEKIA GLOBAL, 2024)
In Bangladesh, vermicomposting has been a popular environmentally friendly composting technique, primarily at small-scale levels. However, few studies have explored the feasibility of medium to large-scale operations. This study establishes a medium-scale vermicompost fertilizer plant in Kushtia, Bangladesh, processing 30 tons of waste monthly to produce 10 tons of fertilizer. Utilizing cow dung from nearby dairy farms and 0.1 million red worms (Eisenia foetida), the experiment runs for three cycles of 120 days each without indoor environmental controls. Over a year, the worm population quadruples to over 0.4 million. Lab tests confirm the fertilizer's pH level (7.69) and nutrient ratios (e.g., 1.792% nitrogen, 0.5217% phosphorus, and 1.514% potassium). The paper includes a cost-benefit analysis, suggesting the viability of such medium-scale setups for green farming in rural Bangladesh.